The effect of anti-frustration ability on academic frustration among Chinese undergraduates: A moderated mediating model - Wu, Minru; Huang, Hua; Fu, Yuanshu; Zhang, Xudong (Frontiers in Psychology, 2023)
The study explores the relationship between college students’ anti-frustration ability (AFA) on their academic frustration (AF) and, especially, the roles of core competence (CC) and coping style (CS) in this relationship. 1500 college students were surveyed. Results show that: (1) AFA could negatively predict the AF of college students, where CC mediated this relationship; (2) CS has a moderating effect on the relationship between CC and AF. We conclude that students who employ positive CS might help alleviate their AF to a larger extent with the mediation of CC.